APLIKASI PENGENALAN HURUF DAN ANGKA, WARNA, SAYURAN DAN BUAH-BUAHAN UNTUK ANAK PAUD BERBASIS SMARTPHONE MENGGUNAKAN METODE LINEAR CONGRUENT(LCM) - Muntahanah, Muntahanah; Imanullah, Muhammad; Pangestu, Irvan Dwi (Jurnal Media Infotama, 2021)
The world of children is a world of play and joy, therefore it is a golden period for them, don't be burdened with things that weigh heavily on their growth and development, therefore don't let them be burdened with learning curricula and tasks that waste their time. The physical factors are that parents who receive a tough education and their great desire for their children to follow what their parents want are burdened and under pressure to obtain perfect results by enrolling their children in tutoring, Early Childhood Education Institutions. (PAUD) because of their principle that achievement shows the success of their parents, especially children at an early age. The Linear Congruent Method (LCM) is a type of PRNG that is widely used in modern computer applications, discovered by D.H Lehmer. This method utilizes a linear model to generate random numbers. Test Results of the Linear Congruent Method (LCM) is easy to learn and implement, besides that it can be applied in other simulation applications, because this algorithm has good speed, it is very efficient in terms of processing time. The shuffling process helps overcome the Linear Congruential Generator (LCG) problem with the independent property (dependence on numbers appearing sequentially), because the resulting numbers are randomized in positi